Negative electrode active material for secondary battery, method for producing the same, negative electrode for secondary battery containing the negative electrode active material, and lithium secondary battery

By sintering natural graphite and forming a carbon coating, the problems of high porosity and low mechanical strength of natural graphite in secondary batteries are solved, and the excellent output and life characteristics of secondary batteries are achieved.

CN113574702BActive Publication Date: 2025-03-25LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080006009.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-18
Filing Date
2020-01-16
Publication Date
2025-03-25
Estimated Expiration
2040-01-16

AI Technical Summary

Technical Problem

Due to the high porosity and low mechanical strength, the natural graphite used in existing secondary batteries has enhanced side reactions with the electrolyte and deteriorated life characteristics, making it difficult to achieve excellent output and life characteristics at the same time.

Method used

By performing a first sintering treatment on the natural graphite, its crystallinity is increased and a carbon coating is formed on its surface and inside, the porosity and surface functional groups are reduced, and mechanical durability is improved.

Benefits of technology

It significantly reduces side reactions with the electrolyte, improves output characteristics and life characteristics, and extends the service life of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003048741420000211
    Figure BDA0003048741420000211
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material for a secondary battery, comprising: natural graphite; and a carbon coating layer formed on the surface and inside of the natural graphite, wherein the negative electrode active material has a porosity of 3% to 13%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is based upon and claims the benefit of priority from Korean Patent Application No. 10-2019-0006527 filed on January 18, 2019, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0004] The present invention relates to a negative electrode active material for a secondary battery, a method for producing the negative electrode active material, and a negative electrode for a secondary battery and a lithium secondary battery comprising the negative electrode active material. Background Art

[0005] As energy prices rise due to the depletion of fossil fuels and concerns about environmental pollution increase significantly, environmentally friendly alternative energy sources become a necessity for future life.

[0006] In particular, with the technological development and increased demand for mobile devices, the demand for secondary batteries as an environmentally friendly alternative energy source is rapidly growing.

[0007] In secondary batteries, lithium metal was originally used as a negative electrode, but since battery short circuit due to dendrite formation and the resulting explosion risk become problems, the use of carbon-based active materials in which lithium ions can be intercalated and deintercalated and maintain structure and electrical properties has been proposed.

[0008] As carbon-based active materials, various forms of carbon-based materials such as artificial graphite, natural graphite and hard carbon have been applied, among which graphite-based active materials are most widely used because they can ensure the life characteristics of lithium secondary batteries due to excellent reversibility. Since graphite-based active materials have a low discharge voltage of -0.2V relative to lithium, batteries using graphite-based active materials can exhibit a high discharge voltage of 3.6V, thereby providing many advantages in terms of energy density of lithium batteries.

[0009] Among these, natural graphite in particular exhibits high output and capacity characteristics relative to other carbon-based active materials, but since it has high porosity and low mechanical strength, a side reaction with an electrolyte becomes strong and life characteristics may deteriorate.

[0010] Therefore, there is a current demand for the development of natural graphite having excellent life performance and high output performance.

[0011] Japanese Patent Registration No. 4403327 discloses a graphite powder for a negative electrode for a lithium ion secondary battery, but does not propose an alternative to the above-mentioned problems.

[0012] [Related technical literature]

[0013] [Patent Document]

[0014] Japanese Patent Registration No. 4403327 Summary of the invention

[0015]

Technical issues

[0016] One aspect of the present invention provides a negative electrode active material for a secondary battery having excellent output characteristics and excellent life characteristics.

[0017] Another aspect of the present invention provides a method for manufacturing a negative electrode active material for a secondary battery having excellent output characteristics and excellent life characteristics.

[0018] Still another aspect of the present invention provides a negative electrode for a secondary battery and a secondary battery including the negative electrode active material for a secondary battery.

[0019]

Technical solution

[0020] According to an exemplary embodiment of the present invention, a negative electrode active material for a secondary battery includes natural graphite; and a carbon coating layer formed on a surface and inside of the natural graphite, wherein the negative electrode active material for a secondary battery has a porosity of 3% to 13%.

[0021] According to another exemplary embodiment of the present invention, a method for manufacturing a negative electrode active material for a secondary battery includes: performing a first calcining treatment on natural graphite at 1,130°C to 1,800°C; mixing the natural graphite subjected to the first calcining treatment and liquid asphalt to form a carbon coating coating the surface and interior of the natural graphite; and performing a second calcining treatment on the natural graphite having the carbon coating formed on its surface and interior.

[0022] According to another exemplary embodiment of the present invention, a negative electrode for a secondary battery includes the above-mentioned negative electrode active material for a secondary battery.

[0023] According to still another exemplary embodiment of the present invention, a lithium secondary battery includes: the above-mentioned negative electrode for a secondary battery; a positive electrode facing the negative electrode for a secondary battery; a separator interposed between the negative electrode for a secondary battery and the positive electrode; and an electrolyte.

[0024]

Beneficial Effects

[0025] The negative electrode active material for a secondary battery of the present invention comprises natural graphite and a carbon coating coating the surface and the interior of the natural graphite, and has a low porosity within a specific range. Therefore, the negative electrode for a secondary battery and the secondary battery comprising the negative electrode active material for a secondary battery of the present invention can prevent side reactions with an electrolyte at a significant level while exhibiting high output characteristics.

[0026] In addition, according to the manufacturing method of the negative electrode active material for secondary batteries of the present invention, natural graphite subjected to the first sintering treatment within a specific temperature range is used as a core, thereby increasing the crystallinity of natural graphite to an appropriate level, thereby improving both the output and life characteristics of natural graphite. In addition, since the carbon coating formed on the surface and inside of natural graphite uses liquid asphalt as a raw material, the coating raw material can penetrate into not only the surface but also the internal pores of natural graphite, thereby, the surface and internal pores of natural graphite can be reduced to an appropriate level to significantly reduce the expansion phenomenon. In addition, the carbon coating formed on the surface and inside of natural graphite can improve the mechanical durability of natural graphite. Therefore, the negative electrode active material for secondary batteries manufactured by the above-mentioned manufacturing method can have both improved high output characteristics and life characteristics. DETAILED DESCRIPTION

[0027] The terms and words used in this specification and claims should not be interpreted as general meanings or dictionary meanings, but should be interpreted as meanings and concepts that satisfy the technical ideas of the present invention based on the principle that the inventors can appropriately define the concepts of the terms in order to describe their own inventions in the best manner.

[0028] The terms used in this specification are only used to describe exemplary embodiments rather than to limit the present invention. Unless the context indicates otherwise, a singular form is intended to include a plural form.

[0029] It should be understood that the terms "comprising", "having" or "having" used in this specification specify the existence of implemented features, numbers, steps, constituent elements or their combinations, but do not exclude the possibility of the existence or addition of one or more other features, numbers, steps, constituent elements or their combinations.

[0030] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured using, for example, laser diffraction. By laser diffraction, particle sizes from approximately the submicron range to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.

[0031] Hereinafter, the present invention will be described in detail.

[0032] <Method for producing negative electrode active material for secondary battery>

[0033] The present invention relates to a method for manufacturing a negative electrode active material for a secondary battery, and in particular to a method for manufacturing a negative electrode active material for a lithium secondary battery.

[0034] The method for manufacturing a negative electrode active material for a secondary battery of the present invention comprises: performing a first calcination treatment on natural graphite at 1,130°C to 1,800°C; mixing the natural graphite subjected to the first calcination treatment and liquid asphalt to form a carbon coating coating the surface and interior of the natural graphite; and performing a second calcination treatment on the natural graphite having the carbon coating formed on its surface and interior.

[0035] According to the manufacturing method of the negative electrode active material for secondary batteries of the present invention, natural graphite subjected to the first sintering treatment within a specific temperature range is used as a core, whereby the crystallinity of natural graphite can be increased to an appropriate level, thereby improving both the output and life characteristics of natural graphite. In addition, since the carbon coating formed on the surface and inside of natural graphite uses liquid asphalt as a raw material, the coating raw material can penetrate into not only the surface but also the internal pores of natural graphite, whereby the surface and internal pores of natural graphite can be reduced to an excellent level and significantly reduce the expansion phenomenon. In addition, the carbon coating formed on the surface and inside of natural graphite can improve the mechanical durability of natural graphite. Therefore, the negative electrode active material for secondary batteries manufactured by the above-mentioned manufacturing method can have both improved high output characteristics and life characteristics.

[0036] The method for producing a negative electrode active material for a secondary battery of the present invention includes subjecting natural graphite to a first calcination treatment at 1,130°C to 1,800°C.

[0037] According to the method for manufacturing a negative electrode active material for a secondary battery of the present invention, the natural graphite is subjected to a first calcination treatment at 1,130°C to 1,800°C before forming a carbon coating layer, thereby increasing the crystallinity of the natural graphite to an appropriate level, reducing the number of functional groups on the surface, and reducing the specific surface area. Therefore, when the first calcination treatment is performed within the above temperature range, side reactions and expansion phenomena with the electrolyte are prevented without hindering the excellent output characteristics of the natural graphite, thereby exhibiting long life characteristics.

[0038] When the first calcination treatment is performed on natural graphite at a temperature lower than 1,130°C, the crystallinity of the natural graphite may not be sufficiently improved and the number of functional groups on the surface and the specific surface area may be reduced at a low level, so that the reaction with the electrolyte may not be sufficiently prevented. When the first calcination treatment is performed on natural graphite at a temperature higher than 1,800°C, the porosity of the natural graphite is too low, making it difficult to ensure a lithium diffusion path, whereby the output characteristics may be excessively deteriorated.

[0039] Specifically, the temperature during the first sintering treatment may preferably be 1,200°C to 1,600°C, more preferably 1,270°C to 1,550°C, in which case the crystallinity and specific surface area of ​​the above-mentioned natural graphite can be adjusted to levels that satisfy the above-mentioned effects, and the obstruction of output characteristics due to excessive improvement in the crystallinity of natural graphite can be prevented, and is therefore more preferred.

[0040] In terms of preventing the occurrence of a side reaction with the electrolyte and an expansion phenomenon, the specific surface area of ​​natural graphite after the first sintering treatment at 1,130° C. to 1,800° C. may be 8.4 m 2 / g or less, preferably 3m 2 / g to 8.4m 2 / g, more preferably 4m 2 / g to 7.4m 2 The "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II available from BEL Japan.

[0041] The average particle size (D 50 ) can be 8μm to 18μm, preferably 10μm to 15μm, and when a negative electrode active material having an average particle size within such a range is used in the negative electrode, it can be filled to an excellent level and the reaction area with the electrolyte can be reduced, thereby maximizing the effect of preventing side reactions with the electrolyte.

[0042] In terms of successfully reducing the specific surface area of ​​natural graphite, the first sintering treatment may be performed in an oxygen atmosphere.

[0043] In consideration of improvement in crystallinity, reduction in specific surface area, etc. of natural graphite, the first sintering treatment may be performed for 5 to 12 hours, preferably 6 to 8 hours.

[0044] The method for producing a negative electrode active material for a secondary battery of the present invention includes mixing natural graphite subjected to a first calcination treatment and liquid pitch to form a carbon coating layer coating the surface and the inside of the natural graphite.

[0045] According to the manufacturing method of the negative electrode active material for secondary batteries of the present invention, the natural graphite treated by the first calcination is coated with liquid asphalt to form a carbon coating, and since the liquid asphalt is used as the coating raw material, the holes can be fully filled from the surface to the inside of the natural graphite compared with the case of using solid asphalt. In addition, as the carbon coating is formed, the surface functional groups of the natural graphite can be further reduced. Therefore, since the porosity of the natural graphite can be reduced to an appropriate level, the effect of preventing the side reaction with the electrolyte and preventing the expansion phenomenon can be improved simultaneously without deteriorating the output characteristics of the natural graphite.

[0046] Furthermore, since a carbon coating is formed on the surface and inside of natural graphite, the overall mechanical durability of the negative electrode active material can be improved, which is preferable for improving life characteristics.

[0047] The liquid asphalt may be a mixture of asphalt and a solvent.

[0048] As the asphalt, coal-based asphalt and / or petroleum-based asphalt may be used without limitation, and preferably, petroleum-based asphalt may be used in terms of excellent cycle stability.

[0049] As the solvent, a solvent that can dissolve asphalt in a wide range, such as tetrahydrofuran (THF), benzene, toluene and / or quinoline, can be used.

[0050] The liquid asphalt may be a mixture of asphalt and solvent in a weight ratio of 50:50 to 95:5, preferably 65:35 to 85:15, taking into account the viscosity of the liquid and the solubility of the asphalt.

[0051] The mixing amount of the liquid pitch may be appropriately designed in overall consideration of the pores and porosity of the natural graphite. For example, the natural graphite and the liquid pitch may be mixed in a weight ratio of 85:15 to 99:1, preferably 90:10 to 97:3.

[0052] Based on the total weight of the negative electrode active material for the secondary battery, 3.5 wt % to 5.5 wt %, preferably 4 wt % to 5 wt % of the carbon coating can be included or formed. Within the above range, the mechanical durability of the negative electrode active material can be improved without hindering the output characteristics of the negative electrode active material, and is therefore preferred.

[0053] As the natural graphite and the liquid pitch are mixed, a carbon coating may be formed on the surface and inside of the natural graphite.

[0054] The method for producing a negative electrode active material for a secondary battery of the present invention includes subjecting natural graphite having a carbon coating layer formed on the surface and inside thereof to a second calcination treatment.

[0055] Through the second calcination treatment, the negative electrode active material including the natural graphite and the carbon coating layer can be graphitized.

[0056] In terms of increasing the crystallinity of the negative electrode active material, the second calcination treatment may be performed under an oxygen atmosphere.

[0057] The second sintering treatment may be performed at 2,800°C to 3,000°C, preferably 2,860°C to 2,940°C, in terms of smoothly performing graphitization and increasing the crystallinity of the negative electrode active material.

[0058] In order to sufficiently perform graphitization, the second sintering treatment may be performed for 3 to 12 hours, preferably 4 to 8 hours.

[0059] Through the second calcination treatment, a negative electrode active material for a secondary battery including a carbon coating layer formed on the surface and inside of natural graphite can be prepared.

[0060] The negative electrode active material for secondary batteries manufactured by the above-mentioned manufacturing method can have a low level of porosity of 3% to 13%, preferably 3% to 10%, more preferably 3% to 8%, and even more preferably 3% to 6%, thereby achieving the excellent output and capacity characteristics of natural graphite, while achieving excellent durability and preventing side reactions with the electrolyte, which is preferred for life characteristics.

[0061] <Negative electrode active material for secondary battery>

[0062] In addition, the present invention provides a negative electrode active material for a secondary battery, specifically a negative electrode active material for a lithium secondary battery. Specifically, the negative electrode active material for a secondary battery can be a negative electrode active material for a secondary battery manufactured by the manufacturing method of the negative electrode active material for a secondary battery.

[0063] Specifically, the negative electrode active material for a secondary battery of the present invention includes natural graphite; and a carbon coating layer formed on the surface and inside of the natural graphite, and has a porosity of 3% to 13%.

[0064] The negative electrode active material for a secondary battery of the present invention comprises a carbon coating layer formed on the surface and inside of natural graphite and has a low level of porosity of 3% to 13%, thereby achieving the excellent output and capacity characteristics of natural graphite while achieving excellent durability and preventing side reactions with an electrolyte, which is preferred for life characteristics.

[0065] The porosity can be calculated by measuring the BET specific surface area of ​​the active material, plotting the BET specific surface area according to the Barrett-Joyner-Halenda (BJH) theory to measure the pore area, and substituting the pore area into the following formula 1. As a BET specific surface area measuring device, BELSORP-mini II (product name, manufactured by Bayer Japan Co., Ltd.) can be used.

[0066] [Formula 1]

[0067] Porosity (%) = pore area / BET specific surface area × 100

[0068] Specifically, the negative electrode active material for a secondary battery of the present invention can be realized according to the method for producing the negative electrode active material for a secondary battery.

[0069] The negative electrode active material for the secondary battery of the present invention may have a porosity of 3% to 13%, preferably 3% to 10%, more preferably 3% to 8%, and even more preferably 3% to 6%. Within this range, both the output characteristics and the life characteristics of the negative electrode active material can be preferably improved. When the porosity of the negative electrode active material is greater than 13%, the side reaction and expansion phenomenon with the electrolyte may be worse, so it is not preferred. In addition, when the porosity of the negative electrode active material is less than 3%, it is difficult to fully ensure the lithium diffusion path, and therefore, the output characteristics may be excessively hindered.

[0070] Based on the total weight of the negative electrode active material for secondary batteries, 3.5 wt % to 5.5 wt %, preferably 4 wt % to 5 wt % of the carbon coating layer may be included. Within this range, it is preferred that improvements in mechanical durability and life characteristics be achieved without hindering the output characteristics of natural graphite.

[0071] In addition, the raw materials, types, sizes, contents, manufacturing methods, etc. of the natural graphite and carbon coating are as described above.

[0072] <Negative electrode for secondary battery and secondary battery>

[0073] Furthermore, the present invention provides a negative electrode for a secondary battery and a secondary battery comprising the negative electrode active material for a secondary battery.

[0074] Specifically, the negative electrode for a secondary battery of the present invention includes: a negative electrode collector; and a negative electrode active material layer formed on the negative electrode collector, and the negative electrode active material layer includes the negative electrode active material for a secondary battery.

[0075] As the negative electrode current collector, a negative electrode current collector commonly used in the art can be used without limitation, for example, as long as the negative electrode current collector has high conductivity and does not cause chemical changes in the lithium secondary battery, there is no particular limitation. For example, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used.

[0076] The negative electrode current collector may have fine concavoconvexities formed on its surface to enhance adhesion with the negative electrode active material, and may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven fabric body.

[0077] The negative electrode current collector may generally have a thickness of 3 μm to 500 μm.

[0078] The negative electrode active material layer is formed on the negative electrode current collector and includes the negative electrode active material for a secondary battery.

[0079] In addition to the negative electrode active material for a lithium secondary battery, the negative electrode active material layer may further include at least one additive selected from the group consisting of a binder, a thickener, and a conductive material.

[0080] The binder is a component that facilitates the bonding of a conductive material, an active material, and a current collector, and may generally be included in an amount of 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer.

[0081] The binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber or a combination of two or more thereof.

[0082] As the thickener, all thickeners conventionally used in lithium secondary batteries can be used, and for example, carboxymethyl cellulose (CMC) or the like can be used.

[0083] The conductive material is a component for further improving conductivity of the negative electrode active material, and may be contained in an amount of 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer.

[0084] The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fibers or metal fibers, fluorocarbons, metal powders such as aluminum and nickel powders, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials include acetylene black series such as products from Chevron Chemical Company, Denka black from Denka Singapore Private Limited, and products from Gulf Oil Company, Ketjen black EC series from Armak Company, Vulcan XC-72 from Cabot Company, Super P from Timcal, etc.

[0085] The negative electrode active material layer may be manufactured by mixing the above negative electrode active material for lithium secondary battery with at least one additive selected from a binder, a conductive material and a thickener in a solvent to prepare a negative electrode slurry, applying the negative electrode slurry on a negative electrode collector, and rolling and drying the applied slurry.

[0086] The solvent may include water or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a solution comprising a negative electrode active material and an optional binder, a conductive material, etc. and a solvent has a preferred viscosity. For example, the solvent may be included in an amount such that the concentration of the solid components comprising the negative electrode active material for the secondary battery and an optional binder, a thickener, and a conductive material is 50% to 95% by weight, preferably 70% to 90% by weight.

[0087] The total pore volume of the negative electrode for the lithium secondary battery can be 7.5 cm 3 / g to 18.5cm 3 / g, preferably 7.5cm 3 / g to 15.5cm 3 / g, more preferably 7.5cm 3 / g to 11cm 3 / g. Within the above range, pores at a sufficient level that do not impede the output characteristics can be ensured, and side reactions with the electrolyte and swelling phenomena can be prevented, so it is preferred. When, for example, measuring the specific surface area of the negative electrode using a BET measurement device, the total pore volume can be measured by a method of measuring the total pore volume according to the Barrett-Joyner-Halenda (BJH) theory.

[0088] Furthermore, the present invention provides a secondary battery, specifically a lithium secondary battery, which includes the negative electrode for a secondary battery described above.

[0089] Specifically, the secondary battery includes: the negative electrode for a secondary battery described above; a positive electrode facing the negative electrode for a secondary battery; a separator disposed between the negative electrode for a secondary battery and the positive electrode; and an electrolyte.

[0090] The positive electrode can be manufactured by coating a positive electrode active material paste containing a positive electrode active material and optionally a binder, a conductive material, a solvent, etc. on a positive electrode current collector, drying the paste, and rolling it.

[0091] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used.

[0092] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium, and specifically may include a lithium composite metal oxide, which includes one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, examples of the lithium composite metal oxide may include lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese-based oxides (such as LiNi 1- Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (such as Li(Ni p Co q Mn r1)O2 (where 0<p<1, 0<q<1, 0<r1<1 and p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2 and p1+q1+r2=2), etc.), or lithium nickel cobalt transition metal (M) oxide (e.g. Li(Ni p2 Co q2 Mn r3 M S2 )O2 (wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo; and p2, q2, r3 and s2 are atomic fractions of each independent element, and 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1), etc.), and may contain any one or more compounds thereof. Among these, in terms of increasing the capacity characteristics and safety of the battery, the lithium composite metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (such as Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and considering the types of constituent elements forming the lithium composite metal oxide and the significance of the improvement effect brought about by the content ratio control, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2、Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., and any one of them or a mixture of two or more thereof can be used.

[0093] Each positive electrode mixture may contain 80 wt % to 99 wt % of the positive electrode active material based on the total weight of the positive electrode mixture.

[0094] The binder is a component that helps to bind active materials, conductive materials, etc. and to bind to the current collector, and is generally added at 1% to 30% by weight based on the total weight of the positive electrode mixture. Examples of the binder include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.

[0095] The conductive material may generally be added in an amount of 1 wt % to 30 wt % based on the total weight of the positive electrode mixture.

[0096] The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, for example, graphite can be used; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials include acetylene black series such as products from Chevron Chemical Company, Danka Black from Danka Singapore Pte Ltd and products from Gulf Oil, Ketjen Black EC series from Ameco, Vulcan XC-72 from Cabot Corporation, Super P from Temeco, etc.

[0097] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a solution containing a positive electrode active material and an optional binder, a conductive material, etc., and the solvent has a preferred viscosity. For example, the solvent may be included in an amount such that the concentration of the solid components containing the positive electrode active material and the optional binder and conductive material is 50% to 95% by weight, preferably 70% to 90% by weight.

[0098] In the lithium secondary battery, the diaphragm separates the negative electrode and the positive electrode and provides a transmission channel for lithium ions, and any diaphragm can be used without particular restrictions, as long as it is generally used as a diaphragm in a lithium secondary battery. In particular, a diaphragm having low resistance to the ion transport of the electrolyte and having excellent electrolyte impregnation ability is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure of two or more films thereof. In addition, conventional porous nonwoven fabrics can be used, for example, nonwoven fabrics made of glass fibers, polyethylene terephthalate fibers, etc. having a high melting point. In addition, a coated diaphragm containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, optionally using a single-layer structure or a multilayer structure.

[0099] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used to manufacture secondary batteries, but are not limited thereto.

[0100] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0101] As the organic solvent, any organic solvent can be used without particular limitation, as long as it can be used as a medium in which the ions involved in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile, such as R-CN (R is a straight chain, branched or cyclic hydrocarbon group of C2 to C20, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone, etc. Among these, carbonate solvents are preferred, and a mixture of cyclic carbonates (e.g., ethylene carbonate, propylene carbonate, etc.) with high ionic conductivity and high dielectric constant to increase the charge / discharge performance of the battery and linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) with low viscosity is more preferred. In this case, when cyclic carbonates and linear carbonates are mixed and used in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.

[0102] The lithium salt can be used without particular limitation, as long as it is a compound capable of providing lithium ions for lithium secondary batteries. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. Preferably, the concentration of the lithium salt is in the range of 0.1M to 2.0M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, so that the electrolyte can exhibit excellent electrolyte properties and lithium ions can be effectively moved.

[0103] As described above, the secondary battery according to the present invention can be used in portable devices such as mobile phones, laptop computers and digital cameras; in the field of electric vehicles such as hybrid electric vehicles (HEV), etc., and can be preferably used as a configuration cell of a medium-to-large battery module. Therefore, the present invention also provides a medium-to-large battery module, which includes the secondary battery described above as a unit cell.

[0104] The medium and large-sized battery module may be preferably applied to power sources requiring large output and large capacity, such as electric vehicles, hybrid electric vehicles, and power storage equipment.

[0105] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments provided in this specification.

[0106] Example

[0107] Example 1: Preparation of negative electrode active material for secondary battery

[0108] Prepare a particle with an average particle size (D 50 ) and subjecting the natural graphite to a first sintering treatment at 1,350° C. for 7 hours.

[0109] As the liquid pitch, a mixed solvent obtained by mixing petroleum-based pitch and THF solvent at a weight ratio of 80:20 and stirring the mixture at 2,000 rpm was used. The natural graphite subjected to the first calcination treatment and the petroleum-based pitch in the liquid pitch were mixed so that the weight ratio was 95.5:4.5. Thus, a carbon coating was formed on the surface and inside of the natural graphite.

[0110] The natural graphite having the carbon coating formed on the surface and inside thereof was subjected to a second calcination treatment at 2,900° C. for 6 hours to produce the secondary battery negative active material of Example 1. The carbon coating was formed at 4.5 wt % based on the total weight of the secondary battery negative active material.

[0111] The negative electrode active material for a secondary battery of Example 1 had a porosity of 5%.

[0112] The porosity is calculated by measuring the BET specific surface area of ​​the negative electrode active material, plotting the BET specific surface area according to the Barrett-Joyner-Halenda (BJH) theory to measure the pore area, and substituting the pore area into the following formula 1. As a BET specific surface area measuring device, BELSORP-mini II (product name, manufactured by Bayer Japan Co., Ltd.) was used.

[0113] [Formula 1]

[0114] Porosity (%) = pore area / BET specific surface area × 100

[0115] Example 2: Preparation of negative electrode active material for secondary battery

[0116] The negative electrode active material for a secondary battery of Example 2 was manufactured in the same manner as in Example 1, except that the first calcination treatment temperature was 1,250° C. The negative electrode active material for a secondary battery of Example 2 had a porosity of 7%.

[0117] Example 3: Preparation of negative electrode active material for secondary battery

[0118] A negative electrode active material for a secondary battery of Example 3 was manufactured in the same manner as in Example 1, except that the first calcination treatment temperature was 1,150°C.

[0119] The negative electrode active material for a secondary battery of Example 3 had a porosity of 9%.

[0120] Example 4: Preparation of negative electrode active material for secondary battery

[0121] A negative electrode active material for a secondary battery of Example 4 was manufactured in the same manner as in Example 1, except that the first calcination treatment temperature was 1,500°C.

[0122] The secondary battery negative electrode active material of Example 4 had a porosity of 4%.

[0123] Comparative Example 1

[0124] A negative electrode active material for a secondary battery of Comparative Example 1 was manufactured in the same manner as in Example 1, except that the first calcination treatment temperature was 1,100°C.

[0125] The secondary battery negative electrode active material of Comparative Example 1 had a porosity of 18%.

[0126] Comparative Example 2

[0127] The negative electrode active material for a secondary battery of Comparative Example 2 is manufactured in the same manner as in Example 1, except that solid asphalt is used instead of liquid asphalt, wherein the solid asphalt is a petroleum-based asphalt, and the natural graphite that has undergone a first calcination treatment and the solid asphalt are mixed in a weight ratio of 95.5:4.5.

[0128] The secondary battery negative electrode active material of Comparative Example 2 had a porosity of 26%.

[0129] Comparative Example 3

[0130] A negative electrode active material for a secondary battery of Comparative Example 3 was manufactured in the same manner as in Comparative Example 2, except that the first calcination treatment temperature was 1,100°C.

[0131] The secondary battery negative electrode active material of Comparative Example 3 had a porosity of 28%.

[0132] Comparative Example 4

[0133] The negative electrode active material for secondary battery of Comparative Example 4 is manufactured in the same manner as in Comparative Example 3, except that the natural graphite that has undergone the first calcination treatment and the solid asphalt are mixed in a weight ratio of 96.5:3.5, and based on the total weight of the negative electrode active material for secondary battery, the carbon coating is formed at 3.5 weight %.

[0134] The secondary battery negative electrode active material of Comparative Example 4 had a porosity of 32%.

[0135] Comparative Example 5

[0136] A negative electrode active material for a secondary battery of Comparative Example 5 was manufactured in the same manner as in Comparative Example 2, except that the first calcination treatment temperature was 1,600°C.

[0137] The secondary battery negative electrode active material of Comparative Example 5 had a porosity of 22%.

[0138] Comparative Example 6

[0139] Prepare a particle with an average particle size (D 50 ) and subjected the artificial graphite to a first sintering treatment at 1,400° C. The artificial graphite subjected to the first sintering treatment and petroleum-based pitch (solid pitch) were mixed at a weight ratio of 95.5:4.5 at 2,000 rpm to form a carbon coating on the artificial graphite.

[0140] The artificial graphite formed with the carbon coating layer was subjected to a sintering treatment at 2,900° C. for 6 hours to produce a secondary battery negative electrode active material of Comparative Example 6. The carbon coating layer was formed at 4.5 wt % based on the total weight of the secondary battery negative electrode active material.

[0141] The secondary battery negative electrode active material of Comparative Example 6 had a porosity of 19%.

[0142] Comparative Example 7

[0143] A negative electrode active material for a secondary battery of Comparative Example 7 was manufactured in the same manner as in Comparative Example 6, except that the first calcination treatment temperature was 1,450°C.

[0144] The secondary battery negative electrode active material of Comparative Example 7 had a porosity of 15%.

[0145] Comparative Example 8

[0146] The negative electrode active material of Comparative Example 8 was prepared in the same manner as in Example 1, except that a negative electrode active material having an average particle size (D 50 )'s artificial graphite replaces natural graphite.

[0147] The secondary battery negative electrode active material of Comparative Example 8 had a porosity of 17%.

[0148] Comparative Example 9

[0149] A negative electrode active material for a secondary battery of Comparative Example 9 was manufactured in the same manner as in Example 1, except that the first calcination treatment temperature was 2,000°C.

[0150] The secondary battery negative electrode active material of Comparative Example 9 had a porosity of 2%.

[0151] <Manufacturing of negative electrode for secondary battery>

[0152] The negative electrode active materials for secondary batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 9, Super C65 as a conductive material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96.6:1:1.3:1.1, and water was added thereto to prepare a negative electrode slurry.

[0153] The negative electrode slurry prepared above was applied to a copper current collector and dried at 130° C. for 10 hours under vacuum to manufacture negative electrodes for secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 9. Here, the loading amount of the negative electrode was 3.61 mAh / cm 2 .

[0154] The total pore volume of the negative electrode for secondary batteries of the above-made embodiments and comparative examples was measured. The total pore volume of the negative electrode for secondary batteries is measured by a method of measuring the total pore volume according to the Barrett-Joyner-Halenda (BJH) theory when measuring the specific surface area of ​​the negative electrode using a BET measuring device (device name: BEL Sorp., manufactured by Bayer Japan Co., Ltd.). The results are shown in Table 1 below.

[0155] <Manufacturing of Secondary Battery>

[0156] LiNi as active material 0.6 Co 0.2 Mn 0.2 O2, Li-435 (manufactured by Danka) as a conductive material, KF9700 (manufactured by Kureha) as a binder, and BM-730H (manufactured by Zeon) as a thickener were mixed at a weight ratio of 96.25:1.0:1.5:1.25, water was added thereto to prepare a positive electrode slurry, which was then applied to an aluminum foil, dried at about 130° C. under vacuum for 8 hours and rolled to manufacture a positive electrode. Here, the positive electrode was manufactured so that its loading was 3.61 mAh / cm 2 .

[0157] A polyolefin separator was placed between each negative electrode manufactured in Examples 1 to 4 and Comparative Examples 1 to 9 and the positive electrode, and then an electrolyte in which 1M LiPF6 was dissolved in a non-aqueous electrolyte solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed in a volume ratio of 1:4 was injected to manufacture each secondary battery of the Examples and Comparative Examples.

[0158] [Table 1]

[0159]

[0160] Experimental Example 1: Evaluation of Swelling

[0161] The secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 9 manufactured above were charged and discharged in the charging range of SOC 0 to SOC 95, wherein the 1st cycle was 0.1 C, the 2nd cycle was 0.2 C, and the 3rd to 30th cycles were 0.5 C. Thereafter, the expansion rate was measured by the following formula 1:

[0162] [Formula 1]

[0163] Expansion rate (%) = (d2-d1) / d1×100

[0164] Here, d1 is the thickness of the negative electrode for a secondary battery before the first charge / discharge cycle is performed, and d2 is the thickness of the negative electrode for a secondary battery after the 30th charge / discharge cycle is performed.

[0165] [Table 2]

[0166] Expansion rate (%) Example 1 18.4 Example 2 19.3 Example 3 20.2 Example 4 18.1 Comparative Example 1 28.9 Comparative Example 2 30.5 Comparative Example 3 31.6 Comparative Example 4 33.8 Comparative Example 5 28.5 Comparative Example 6 27.3 Comparative Example 7 25.6 Comparative Example 8 25.4 Comparative Example 9 18.1

[0167] Referring to Table 2, it was confirmed that, compared with the comparative example, in the negative electrode active materials for secondary batteries of Examples 1 to 4 manufactured by mixing natural graphite that had undergone a first calcination treatment at 1,130°C to 1,800°C and liquid asphalt to form a carbon coating coating the surface and interior of the natural graphite and performing a second calcination treatment, side reactions with the electrolyte were significantly prevented and the expansion phenomenon was reduced.

[0168] Experimental Example 2: Output Evaluation

[0169] The output characteristics of the secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 9 manufactured above were evaluated. The output characteristics were evaluated by setting the secondary batteries of Examples and Comparative Examples to SOC 50 according to the hybrid pulse power characteristics (HPPC) test method and measuring the output resistance at room temperature (25°C).

[0170] Specifically, the secondary battery was charged and discharged for 3 cycles at 0.33 C under the conditions of discharging at 2.5 V and charging at 4.2 V. Thereafter, from the state of discharging to SOC 50, the battery was charged to 2.5 C (10 minutes), stopped (30 minutes), discharged to 2.5 C (10 minutes), and stopped (30 minutes), and the voltage change during charge / discharge was divided by the applied current to measure the output resistance.

[0171] [Table 3]

[0172] Output resistance (ohms) Example 1 0.71 Example 2 0.75 Example 3 0.80 Example 4 0.72 Comparative Example 1 0.94 Comparative Example 2 1.01 Comparative Example 3 1.05 Comparative Example 4 1.12 Comparative Example 5 1.26 Comparative Example 6 1.41 Comparative Example 7 1.79 Comparative Example 8 1.77 Comparative Example 9 1.54

[0173] Referring to Table 3, it was confirmed that the negative electrode active materials for secondary batteries of Examples 1 to 4, which were manufactured by mixing natural graphite that had undergone a first calcination treatment at 1,130°C to 1,800°C and liquid asphalt to form a carbon coating coating the surface and interior of the natural graphite and performing a second calcination treatment, also showed excellent performance in output characteristics compared to the comparative example.

Claims

1. A negative electrode active material for a secondary battery, comprising: Natural graphite; and A carbon coating is formed on the surface and inside of the natural graphite, wherein The negative electrode active material for a secondary battery has a porosity of 3% to 13%, and Wherein, based on the total weight of the negative electrode active material for secondary battery, the carbon coating layer is contained in an amount of 3.5 wt % to 5.5 wt %, The porosity is calculated by measuring the BET specific surface area of ​​the active material, plotting the BET specific surface area according to the BJH theory to measure the pore area, and substituting the pore area into the following formula 1: [Formula 1] Porosity (%) = pore area / BET specific surface area × 100.

2. A method for producing a negative electrode active material for a secondary battery according to claim 1, the method comprising: A first sintering treatment of natural graphite at 1,130°C to 1,800°C; Mixing the natural graphite subjected to the first sintering treatment and liquid asphalt to form a carbon coating coating the surface and interior of the natural graphite; and The natural graphite having the carbon coating formed on the surface and inside thereof is subjected to a second sintering treatment. 3 . The method for producing a negative electrode active material for a secondary battery according to claim 2 , wherein the first calcination treatment is performed at 1,200° C. to 1,600° C. 4 . The method for producing a negative electrode active material for a secondary battery according to claim 2 , wherein the first calcination treatment is performed for 5 to 12 hours. 5 . The method for producing a negative electrode active material for a secondary battery according to claim 2 , wherein the second calcination treatment is performed at 2,800° C. to 3,000° C. 6 . The method for producing a negative electrode active material for a secondary battery according to claim 2 , wherein the second calcination treatment is performed for 3 to 12 hours.

7. The method for producing a negative electrode active material for a secondary battery according to claim 2, wherein the natural graphite has an average particle size D of 8 μm to 18 μm. 50 . 8 . The method for manufacturing a negative electrode active material for a secondary battery according to claim 2 , wherein the carbon coating layer is formed at 3.5 wt % to 5.5 wt % based on the total weight of the negative electrode active material for a secondary battery. 9 . A negative electrode for a secondary battery, comprising the negative electrode active material for a secondary battery according to claim 1 .

10. The negative electrode for a secondary battery according to claim 9, wherein the negative electrode for a secondary battery has a thickness of 7.5 cm 3 / g to 18.5cm 3 / g total pore volume.

11. A lithium secondary battery comprising: The negative electrode for a secondary battery according to claim 9; a positive electrode facing the negative electrode for a secondary battery; a separator disposed between the negative electrode for the secondary battery and the positive electrode; and Electrolytes.

Citation Information

Patent Citations

  • How to repair a short circuit in a TFT substrate

    KR1020190006527A

  • Negative electrode carbon material for non-aqueous secondary battery, negative electrode, and non-aqueous secondary battery

    CN103477476A

  • Anode active material for lithium secondary battery, and method for preparing anode active material

    CN106450163A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    EP2913299A1

  • Material for lithium ion secondary battery negative electrode, manufacturing method thereof, lithium ion secondary battery negative electrode, and lithium ion secondary battery

    JP2014170724A